The relationship between test anxiety and pre-service teachers’ performance in quantitative research methods - Butakor, Paul Kwame; Mingah, Oscar (Journal of Education and Learning (EduLearn), 2024)
The mere mention of mathematics and its related courses such as quantitative research methods drive down shivers and create anxiety among most students. However, this phenomenon has not will been addressed among preservice teachers. The purpose of this study was to examine the relationship between preservice teachers test anxiety and performance in quantitative research methods in education. And to achieve this purpose, a random sample of 313 preservice teachers from a teacher education University in Ghana were administered the test anxiety inventory (TAI) and the data analysed using both descriptive and inferential statistics. The results revealed a significant inverse relationship between test anxiety and preservice teachers’ performance. Similarly, factors such as the examiner, the exam format, previous failures, examination time, presence of invigilator, and lack of adequate preparations were identified as determinants of test anxiety. In terms of coping strategies, it was revealed that respondents adopted cognitive, and educational strategies to mitigate the effect of test anxiety.